“We’ll Always Have Paris”: Out-of-Country Buyers in the Housing Market - Cvijanović, Dragana; Spaenjers, Christophe (Management Science, 2021)
Previous research has shown that nonlocal household investors make suboptimal asset selection and market timing decisions. However, in real estate markets, heterogeneity in returns can exist even with identical ex ante investment (timing) choices, given that transaction prices are the outcome of a complex search-and-bargaining process. Analyzing notarial data for the Paris housing market, we find that “out-of-country” buyers indeed buy at higher prices and resell at substantially lower prices than do local investors, ceteris paribus. Furthermore, our evidence suggests that this pattern is not due to higher search costs and information asymmetries but instead stems from wealth-related differences in bargaining intensity. Finally, we estimate the causal effect of out-of-country demand shocks on property prices in Paris to be positive but small. This paper was accepted by Tomasz Piskorski, finance.